Cell-Free Biocatalysis for the Production of Platform Chemicals - Bergquist, Peter L.; Siddiqui, Sana; Sunna, Anwar (Frontiers in Energy Research, 2020)
Genetically engineered host bacteria have an extensive history for the production of specific proteins including the synthesis of single enzymes for the modification of compounds produced for industrial purposes by biological or chemical processes. Such processes have been developed largely through the process of discovery. The ability to assemble multiple enzymes into synthetic pathways is a new development aided by the synthetic biology approach of constructing and assembling suitable enzymes into pathways that may or may not occur in Nature to provide a high-impact platform for bio-manufacturing of chemicals, biofuels and pharmaceuticals. Industry has depended on chemical catalysts because of the known constraints experienced frequently with biological catalysts but when high stereochemistry, mild synthesis conditions and environmentally friendly processes are significant, application of enzymes is preferred, especially in the case of drug synthesis where enantioselectivity is important. However, many whole cell production processes are beset by toxicity problems, metabolite competition, the production of side products, sub-optimal enzyme ratios and varying temperature optima. As a result, a cell-free biocatalysis allows the manipulation of substrate ratios, provision of regenerated cofactors and adjustment of high energy flux ratios that are difficult or impossible to control in whole cell synthesis. We discuss here the construction of cell free biocatalytic pathways as added free enzymes or multi-enzyme modules that may contain heterologous catalysts. We examine the status of applications leading to commercialisation, emphasizing the importance of economical cofactor regeneration. Nevertheless, problems remain, particularly protein post-translational modifications including glycosylation, phosphorylation, ubiquitination, acetylation, proteolysis, etc. The National Renewable Energy Laboratory and Pacific North West Laboratory have published lists of top value-added chemicals from biomass that include glucaric acid. There have been few reports on the combination of synthetic biology and cell-free protein synthesis to set up pathways for these valuable intermediate compounds. This observation is despite the existence of at least one large scale but specialized cell-free production of antibody conjugates. This review will provide a description of one successful attempt at the cell-free production of glucaric acid and will evaluate progress for other key intermediate and platform chemicals.